The New Order Political Policy: The Prohibition of Literature Work by The Indonesian Government in 1966-1998 - Sari, Laila; Marjono, Marjono; Sumardi, Sumardi; Umamah, Nurul; Surya, Riza Afita (JURNAL HISTORICA, 2022)
Embodiment of national stability was the main step taken by the New Order during his reign (1966-1998). The realization of national stability in the field of culture is carried out by prohibiting literary works that disturb national stability. The purpose of this study was to determine the background, implementation and impact of the policy of banning literary works. This study uses historical research methods and political institutionalism approaches. The results of the study indicate that the background of the policy on the prohibition of literary works is the emergence of literary resistance. The implementation of the policy on the prohibition of literary works in the form of the prohibition of literary books and the detention of writers. The impact of the policy on the prohibition of literary works has an impact on the print media industry and the fate of Indonesian writers and literary works.